2014
DOI: 10.1155/2014/323657
|View full text |Cite
|
Sign up to set email alerts
|

Genital Infection with Herpes Simplex Virus Types 1 and 2 in Women from Natal, Brazil

Abstract: Objective. To evaluate the prevalence of HSV-1 and HSV-2 in pregnant and nonpregnant women, testing the correlation between DNA of the viruses with colposcopic and/or cytological changes, and evaluate association with sociodemographic characteristics and sexual activity. Methods. Included in this study were 106 pregnant and 130 nonpregnant women treated at primary health care units of Natal, Brazil, in the period 2010-2011. The patients were examined by colposcopy, and two cervical specimens were collected: on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…HHV-2 seroprevalence found (20.6%) was greater than that of anti-HHV-2 in pregnant women in Northeast India (8.7 %) (Biswas et al 2011), which is compared to pregnant women from the Northwestern Region of Brazil (12.3%) (Miranda et al, 2014) and to the global prevalence of women (14.8%) (Looker et al, 2015). In this research, pregnant women under 30 years old showed 3.8 times less chance to be exposed to HHV-2 compared to those above 30 years old (ODDS: 3.8;…”
Section: Genital Herpes Is a Sexually Transmitted Infection (Ist)mentioning
confidence: 67%
“…HHV-2 seroprevalence found (20.6%) was greater than that of anti-HHV-2 in pregnant women in Northeast India (8.7 %) (Biswas et al 2011), which is compared to pregnant women from the Northwestern Region of Brazil (12.3%) (Miranda et al, 2014) and to the global prevalence of women (14.8%) (Looker et al, 2015). In this research, pregnant women under 30 years old showed 3.8 times less chance to be exposed to HHV-2 compared to those above 30 years old (ODDS: 3.8;…”
Section: Genital Herpes Is a Sexually Transmitted Infection (Ist)mentioning
confidence: 67%
“…In HSV-2-induced infection, TAM receptor expression may favor cell susceptibility to ZIKV (entry) as well as permissivity resulting from inflammation ( Figure 4 : Tropism benefit) [ 98 ]. Interestingly, Brazil’s northern region, which has a high number of ZIKV-related microcephaly cases, is also an area with strong seroprevalence for HSV-1 and HSV-2 ( Figure 4 : Epidemiology influence) [ 50 , 149 , 151 , 153 ].…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
“…Herpes simplex virus (HSV) is a neurotropic virus that possesses a large linear, double-stranded DNA genome, which is presented in the form of two distinct serotypes: HSV-1 and HSV-2 (116). HSV often infects the mucosa of the mouth, eyes and the human anogenital tract (117).…”
Section: Oncolytic Virotherapymentioning
confidence: 99%